Numerical simulation and protection of the dynamic change of Jinan karst spring based on coupling of seepage and conduit flow. Issue 9 (September 2022) - Li, Changsuo; Xing, Liting; Dong, Yanan; Peng, Yuming; Xing, Xuerui; Li, Chuanlei; Zhao, Zhenhua
Abstract: The objective of this study was to predict the dynamic change in the spring water level more precisely, to provide timely solutions for karst spring protection. Using the Jinan spring region as a case study, this study established a numerical model of a karst groundwater system, and optimized the mining layout. The calculated maximum extraction volume following the optimized exploitation layout was 0.69 m 3 /s, in order to ensure the continuous flow of spring water in the median water year. A coupled karst groundwater numerical model with dual structure was developed using the MODFLOW-Conduit Flow Process (CFP), which simulates and then precisely predicts changes in the water level of the karst springs. Here, the plane extension direction of the karst conduit was determined by a tracer test and correlation analysis of the spring water levels and groundwater levels of the observation wells. Meanwhile, the vertical location of the karst conduit was determined by layered monitoring of the groundwater temperature and conductivity. Based on this, a coupling model of seepage and conduit flow was created to simulate the dynamic change in the spring water level, and the dual-media coupling model improved the simulation accuracy of the spring water level. The current study confirmed that, compared to the porous media seepage model, the dual-media coupling model can simulate the groundwater level dynamic change more accurately in a heterogeneous karst aquifer in northern China. The coupling model was used to analyze the effect of supplementation and optimize mining, to ensure that spring water continues to flow during the dry season while supplying the mining demand. Abstract : Coupling model; Jinan; Karst water; Spring protection.